Community-Based Nutrition Education and Local Food Innovation for Stunting Prevention among Pregnant Women - Eka Purwasari; Dian Haerani; Ergawati; Fika Zahara; Irawati; Nani Nasihah; Sunengsih; Rini Kundaryanti (Rajaki of Tulip Medika Publisher, 2026)
Stunting remains a critical public health problem with long-term impacts on child growth, cognitive development, and future productivity, particularly in vulnerable communities. Prevention strategies need to be initiated during pregnancy by improving maternal knowledge and nutritional practices through community-based interventions. This community service program aimed to improve pregnant women’s knowledge on stunting prevention through nutrition education combined with local food innovation. The program was implemented at a community health post and involved 30 pregnant women as participants. The intervention included health education sessions on stunting prevention and a practical demonstration of a local food innovation using purple sweet potato pudding as a nutritious supplementary food. Program evaluation was conducted using a pretest–posttest approach to assess changes in participants’ knowledge, supported by participatory observation and direct feedback to evaluate the acceptability of the food innovation. The results showed a significant increase in knowledge, with the mean score improving from 67.7 before the intervention to 90.7 after the program. Participants also demonstrated positive responses toward the local food innovation, perceiving it as easy to prepare, acceptable in taste, and feasible for daily consumption during pregnancy. In conclusion, community-based nutrition education integrated with local food innovation is an effective and practical approach to support stunting prevention among pregnant women and has the potential to be applied more widely within community health services.